Paleontology: paths to research, science and professional training in Brazil (Terr@ Plural, 2021)
The purpose of this paper is to describe concisely the creation, organization, and management of a research group in the field of paleontology relevant to science in Brazil that has survived for two decades. The Palaios Stratigraphic Paleontology UEPG/CNPq group completed 20 years in 2020 with a background marked by the enthusiasm and feelings that science in Brazil is made through a lot of effort, investigation, dedication, and group work. At last, the historical context shapes this article, and direct or indirect mishaps mark the path of this group that has consolidated itself in different national and international universities with roots in the State University of Ponta Grossa.
Keywords: Science; Research Group; Science History